The Value of Things : Prehistoric to Contemporary Commodities in the Maya Region - Mathews, Jennifer P., 1969-; Guderjan, Thomas H. (Book collections on Project MUSE., 2017)
"This book explores how the Mayans gave value to commodities through the lens of anthropology and archaeology"--Provided by publisher.